HLA restriction of human cytotoxic T lymphocytes specific for influenza virus. Poor recognition of virus associated with HLA A2 (The Rockefeller University Press, 1978)
Cytotoxic T lymphocytes (CTL), specific for influenza A/X31 virus, were generated from human peripheral blood lymphocytes. These CTL lysed target cells that were infected with the same virus and that shared HLA A or B locus antigens. Minimal lysis was observed when HLA-D antigens were shared. Not all HLA A and B antigens were equally effective. Efficient lysis of target cells was seen when HLA A1, A3, B7, B8, B27 and BW21 were shared with the CTL, but when HLA A2 was the only shared antigen lysis was usually minimal. This deficiency in CTL function associated with HLA A2 was not absolute. It is suggested that the function of this antigen might be influenced by other surface molecules on the cell and in particular the other HLA products.